Pengelolaan Lingkungan Pesisir Melalui Aksi Bersih Sampah sebagai Upaya Konservasi di Wisata Pantai Putih Kabupaten Manokwari, Papua Barat - Paradida, Yulia Putri; Tarigan, Marsten Lihardo; Luhulima, Fiona Djunita Natalia; Ansiska, Paisal (Jurnal Pengabdian Arumbai, 2023)
Pasir Putih Beach in Manokwari Regency, West Papua is an attractive natural tourist destination with soft sand, clear water and stunning natural views, attracting both local and international tourists. However, its natural charm is disturbed by a serious problem, namely the presence of rubbish on the beach, especially plastic waste such as bottles, bags and single-use food containers which are often scattered around the beach. It is important to manage waste on beaches with specific measures, including regular cleaning programs, raising public awareness, and conducting environmental education campaigns. The main aim of this activity is to increase the awareness and responsibility of students, the community and tourists in protecting the coastal environment in Manokwari Regency, especially in the White Beach Tourism. This community service activity was held at Pasir Putih Beach Tourism, Manokwari Regency, West Papua. The event was held on Sunday, June 3 2023, and included the stages of socializing plans, coordinating and implementing activities to achieve the set goals. The service program shows a strong commitment to maintaining the beauty of White Beach. Involving Indonesian and English literature students brings rich perspectives on environmental issues. The success of the activity reflects the synergy of education, public awareness and real action to protect the coastal environment. Manokwari Regency is an example of environmental protection, it is hoped that people will be responsible for nature. This program opens the door to positive change and harmony between humans and nature.